Cavernous Hemangiomas of the Internal Auditory Canal and Cerebellopontine Angle. Issue 1 (January 2015) - Oldenburg, Michael S.; Carlson, Matthew L.; Van Abel, Kathryn M.; Giannini, Caterina; Jacob, Jeffrey; Rivas, Alejandro; Driscoll, Colin L.; Link, Michael J.
Abstract : Objective: To review the clinical presentation, differential diagnosis, management strategy, and outcomes after microsurgical resection of cavernous hemangiomas (CHs) arising primarily within the internal auditory canal (IAC) and cerebellopontine angle (CPA). Patients: Twelve patients (10 men; aged 18–66 yr) were included from 1982 to 2012 from one of two tertiary academic referral centers. Intervention(s): All patients underwent preoperative imaging evaluation and subsequent microsurgical resection. Main Outcome Measure(s): American Academy of Otolaryngology-Head and Neck Surgery hearing class, facial nerve function, and tumor control. Results: The most common presenting symptoms were ipsilateral sensorineural hearing loss, nonpulsatile tinnitus, and vertigo. Three presented with facial paresis, 10 had lost serviceable hearing preoperatively. All lesions demonstrated heterogeneous enhancement with gadolinium and hyperintense signal on T2-weighted imaging. The median tumor diameter was 8 mm; eight CHs were confined to the IAC, whereas four involved the CPA. Tumors were accessed via a translabyrinthine approach in eight cases, retrosigmoid craniotomy in three cases, and a middle cranial fossa approach in one case. Ten patients received gross total resection, whereas two underwent subtotal removal. Neither patient with serviceable preoperative hearing retained useful hearing after resection. Eight of the nine patients with normal preoperative facial nerve function retained House-Brackmann grade 1 function after surgery. One patient had residual tumor treated with postoperative stereotactic radiosurgery. Conclusions: Primary CHs of the IAC and CPA are rare and present clinically and radiographically similar to vestibular schwannoma. Microsurgical resection provides excellent facial nerve outcomes and tumor control for most patients; however, the majority of individuals will acquire non-serviceable hearing either from disease or as a result of treatment.